2019
DOI: 10.1055/s-0038-1661423
|View full text |Cite
|
Sign up to set email alerts
|

Common Topics of Publication and Levels of Evidence in the Current Hand Surgery Literature

Abstract: Background Scientific publications are the primary vehicle for the distribution of scientific findings, but there has been limited research on literature topic surveillance. We sought to identify and characterize the most commonly published topic domains in the hand surgery literature. Methods We performed a 6-month hypothesis testing phase to identify the most frequently published topics in three hand surgery journals: Hand, The Journal of Hand Surgery (American), and The Journal of Hand Surgery (Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…They concluded that this small subset of topics constitutes an outsized proportion of the hand surgery publications. 9 Our study found similar results, with 23.2% of all articles published coming from 3 topics in a 5.5-year time frame. The clinical relevance and economic burden of these 3 topic domains might explain why they are the most commonly published in foot and ankle literature.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…They concluded that this small subset of topics constitutes an outsized proportion of the hand surgery publications. 9 Our study found similar results, with 23.2% of all articles published coming from 3 topics in a 5.5-year time frame. The clinical relevance and economic burden of these 3 topic domains might explain why they are the most commonly published in foot and ankle literature.…”
Section: Discussionsupporting
confidence: 84%
“…For these reasons, it is important to assess and critically analyze the type and the quality of data being published within each specialty. Recently, Lemme et al 9 looked at the common topics published in hand surgery and noted that the majority (27%) of articles published in a 5-year period were in 3 specific topics. They concluded that this small subset of topics constitutes an outsized proportion of the hand surgery publications.…”
Section: Discussionmentioning
confidence: 99%
“…However, it can be difficult for surgeons to stay up to date on the latest research. [4][5][6][7][8][9] Literature reviews can help clinicians process a large number of studies more quickly, but conducting these reviews by traditional methods is time-consuming and prone to error. [10][11][12] This study seeks to utilize advances in machine This study successfully utilized machine learning to process 11,501 articles and reduced these studies to 50 topics ranked by overall frequency and trends in frequency from 2000-2021.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Today, more articles are published in hand surgery journals than ever before, making it difficult for practicing surgeons to sort through the evergrowing body of literature. 4,5 Modern health systems emphasize evidence-based treatment, and expect their physicians to stay updated on and comply to the latest standards of care. [6][7][8][9] Therefore, it is critical that clinicians and researchers are able to efficiently process trends in research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation